Resistive switching properties of Mn-doped amorphous Nb2O5 thin films for resistive RAM application - Tsai, Meng-Hung; Shih, Chia-Jung; Chang, Che-Wei; Chu, Yu-Tseng; Wu, You-Shen; Huang, Cheng-Liang (Materials science in semiconductor processing, 2022)
In this work, based on the calculation of the band gap of amorphous Nb2O5, we proposed that the amorphization in Nb2O5 thin films could narrow the band gap. As a proof of concept, amorphous Nb2O5 based resistive random-access memory devices were fabricated. In addition to the amorphization effect, the influence of Mn dopants and temperature on the conduction mechanism of the Nb2O5-based devices were investigated. Furthermore, oxygen vacancies were demonstrated to dominate the conduction mechanism of the Mn-doped Nb2O5-based devices. The oxidation states of O, Nb, and Mn analyzed by X-ray photoelectron spectroscopy signifying that the Mn addition was conducive to the oxidation of Nb during the conduction formation process, consequently offering immense benefits for the improvement of RRAM memory performance.